Whose roads? Defining bicyclists' and pedestrians' right to use public roadways. - Litman, Todd (My University, 2004)
Many people believe that nonmotorized modes (walking, cycling, and their variations) have an inferior right to use public roads compared with motor vehicles. This reflects the belief that motor vehicles are more important to society than nonmotorized modes, and that roads are funded by motorists. This paper investigates these assumptions. It finds that nonmotorized modes have the legal right to use public roads, that nonmotorized modes provide significant transportation benefits, and pedestrians and cyclists pay a significant share of roadway costs. Although motorist user fees (fuel taxes and vehicle registration fees) fund most highway expenses, funding for local roads (the roads pedestrians and cyclists use most) originates mainly from general taxes. Since bicycling and walking impose lower roadway costs than motorized modes, people who rely primarily on nonmotorized modes tend to overpay their fair share of roadway costs and subsidize motorists.
Keywords: Individualverkehr; Fahrradverkehr; Fußgänger; Kosten-Nutzen-Analyse; Radverkehrsförderung; Verkehrsregel; Nutzungsrecht